2015
DOI: 10.1002/srin.201500008
|View full text |Cite
|
Sign up to set email alerts
|

Combination of In Situ Microscopy and Calorimetry to Study Austenite Decomposition in Inclusion Engineered Steels

Abstract: In situ high temperature confocal laser scanning microscopy and differential scanning calorimetry studies of ferrite formation in inclusion engineered (Ti2O3 and TiN) steels have been performed. The applied methodology allows distinction between intragranular ferrite, grain boundary ferrite, and pearlite. The effect of the inclusions and cooling rates on the initiation of phase transformation and the final microstructure is discussed. It is concluded that the applied hybrid methodology could provide vital deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The formation of IGF could improve the properties of the steels, such as toughness. Several review papers have discussed this topic . In our previous study, the IGF formation and the inclusion characteristics have been discussed in steels with Ti 2 O 3 and TiO 2 additions.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of IGF could improve the properties of the steels, such as toughness. Several review papers have discussed this topic . In our previous study, the IGF formation and the inclusion characteristics have been discussed in steels with Ti 2 O 3 and TiO 2 additions.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the second peak could be observed in the Fe–0.4 mass% C alloy. In our previous study, the first peak is identified as the ferrite formation, and the second peak is identified as the pearlite formation. It is also noted that the second peak in the Fe–0.4 mass% C alloy increases sharply with the increase of the carbon content.…”
Section: Discussionmentioning
confidence: 96%
“…The DSC apparatus was used, as was reported by Nakajima et al, Zhang et al, and Mu et al During the sample preparation, the steel specimens were cut into small discs (4.1 mm in diameter and 1 mm in depth). Therefore, the disc shape sample was set into an alumina crucible (Ф 5.5 mm O.D.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations